Reviewing the Role of Physiological Data in Immersive Environments: A Rapid Systematic Review - Melo, Edel Da Silva; Trevisan, Daniela Gorski; Saade, Débora Christina Muchaluat (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
This systematic literature review investigates the use of physiological signals for evaluating user experience (UX) in immersive environments such as virtual reality (VR), augmented reality, and extended reality (XR). Drawing from 118 peer-reviewed articles published between 2019 and 2024, the study identifies the most commonly used biosignals, collection devices, evaluation criteria, and supporting instruments. Key physiological measures include electrodermal activity (EDA), heart rate (HR), heart rate variability (HRV), and electroencephalography (EEG), which are frequently associated with emotional responses, cognitive load, and presence. The analysis, conducted through rapid review, highlights a strong reliance on hybrid approaches that combine physiological data with subjective questionnaires and behavioral metrics. While emotion and cybersickness emerge as dominant UX evaluation dimensions, the study also reveals ethical gaps in research reporting. By mapping the interconnections between technologies, signals, and evaluation frameworks, this review offers a comprehensive overview of current trends and provides practical insights for researchers aiming to develop more adaptive and user-centered immersive systems.